Strengthening Global Health Through One Health - Svensson, Anna; Winder, Marie; Bjorkman, Cleveland Monika; öderholm, Minguez (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2025)
This study examines the implementation of the One Health paradigm in Sweden, which integrates human, animal, and environmental health sectors to address global health challenges. The primary research objective is to explore how Sweden has applied the One Health approach to manage zoonotic diseases, antimicrobial resistance (AMR), and the health impacts of climate change. Using a descriptive case study methodology, data were collected through documentary analysis and semi-structured interviews with 17 respondents from key institutions such as Karolinska Institutet, the Swedish University of Agricultural Sciences (SLU), and the Swedish National Veterinary Institute. The findings reveal that Sweden has made significant strides in cross-sectoral collaboration, enhanced surveillance systems, and improved policy responses, particularly in managing zoonotic diseases and controlling AMR. Sweden’s framework for data sharing and coordination between sectors serves as a model for other nations facing similar health challenges. The study identifies Sweden's approach to addressing climate change as part of the One Health framework as a critical contribution to global health. Future research should focus on overcoming barriers to local-level collaboration, improving data-sharing mechanisms, and developing real-time coordination strategies to further strengthen the One Health approach globally.